Temporal trends in alcohol, cannabis, and simultaneous use among 12th‐grade U.S. adolescents from 2000 to 2020: Differences by sex, parental education, and race and ethnicity. (20th September 2022) - Keyes, Katherine M.; Kaur, Navdep; Kreski, Noah T.; Chen, Qixuan; Martins, Silvia S.; Hasin, Deborah; Olfson, Mark; Mauro, Pia M.
Abstract: Background: Simultaneous use of alcohol and cannabis to enhance each other's effect can cause potential harm. Time trends are diverging in adolescent use of alcohol, which is declining, and cannabis, which is increasing among certain subgroups. However, little is known about trends in their simultaneous and non‐simultaneous use. Racial and socioeconomic disparities are emerging in cannabis use, which may portend consequences to public health. Methods: The 2000 to 2020 Monitoring the Future surveys included approximately 38, 000 U.S. 12th‐grade students with information on simultaneous use and pertinent demographic factors. A 5‐level alcohol/cannabis measure included past‐year simultaneous use (i.e., alcohol and cannabis use at the same time), non‐simultaneous alcohol and cannabis use, alcohol‐use‐only, cannabis‐use‐only, and no use. Multinomial logistic regressions estimated associations (adjusted relative risk ratios; aRRR) with time period (2000 to 2004, 2005 to 2009, 2010 to 2014, 2015 to 2020). Models were adjusted and included interactions with sex, race/ethnicity, and parental education. Results: Between 2000 and 2020, simultaneous alcohol/cannabis use among 12th graders decreased from 24.4% to 18.7%. From 2015 to 2020 compared to 2000 to 2004, the odds of simultaneous use (adjusted relative risk ratio (aRRR) vs. no use = 0.57, 95% CI [0.50, 0.66]) and alcohol‐use‐only (aRRR = 0.55, 95% CI [0.49, 0.61]) decreased, while cannabis‐use‐only odds increased (aRRR = 2.59, 95% CI [1.87, 3.59]). Notably, the prevalence of cannabis‐use‐only more than doubled from 2011 to 2019. The odds of simultaneous use, alcohol‐use‐only, and non‐simultaneous use of alcohol and cannabis declined more rapidly among males than females, whereas the odds for cannabis‐use‐only increased faster for females than males. Increases in cannabis‐use‐only were faster for non‐white adolescents. Conclusion: Simultaneous use of alcohol and cannabis is declining among U.S. adolescents, but the decline is slower among females than males. Declines in simultaneous use are largely concomitant with historical declines in alcohol use, indicating that a continued focus on reducing alcohol use among adolescents and young adults has extended benefits to other adolescent substance use. However, cannabis use without any reported past‐year alcohol use more than doubled in the last decade, a concerning trend. Abstract : Simultaneous use of alcohol and cannabis is declining among US adolescents, but this decline is slower among females than males. Declines in simultaneous use are largely concomitant with historical declines in alcohol use, indicating that continued focus on reducing alcohol among adolescents and young adults has extended benefits to other adolescent substance use. However, cannabis use without any reported past‐year alcohol use more than doubled in the last decade, a concerning trend.